Prevalence of global physical activity among young people: an updated systematic review for the Brazil's Report Card - Valter Cordeiro Barbosa Filho; Rafael Martins da Costa; Bruno Nunes de Oliveira; Victor Hugo Santos de Castro; Kelly Samara da Silva (Universidade Federal de Santa Catarina, 2021)
This study aimed to update the review of Brazil's Report Card on the prevalence of global physical activity (PA) among Brazilian children and adolescents. This systematic review included an electronic search of eight databases (PubMed, Scopus, Web of Science, LILACS, SPORTDiscus, BIREME, Scielo, and Google Scholar) and a manual search of the references of retrieved studies. Studies published in 2018 and 2019 that assessed global PA among Brazilian youth were included. A narrative approach to the results was adopted. The initial search retrieved 1,892 potentially relevant titles (1,244 titles after duplicate analysis), of which 62 (47 different studies) met all the inclusion criteria. Most updated studies were carried out in Southern (40.4%) and Southeastern (25.5%) Brazil. Six studies provided data from national surveys (12.8%), and one study included preschool children (< 5 years old). Ten studies objectively measured PA (accelerometer or pedometer devices). In the updated studies, the overall proportion of young people who were physically active ranged from 9.8% to 79.6%. Three national surveys reported the prevalence of physically active students, ranging from 18.4% to 78.8%. There was an increase of surveys that objectively measured PA and with children under 12 years of age in the 2018 and 2019 studies. However, important research gaps (e.g., variations in the measurement of global PA), even in the same study, should be considered to improve the monitoring and evaluation of global PA in Brazil.